Absolute lymphocyte count on the first day of thymoglobulin predicts relapse-free survival in matched unrelated peripheral blood stem cell transplantation. Issue 13 (9th November 2020) - Modi, Dipenkumar; Kim, Seongho; Surapaneni, Malini; Ayash, Lois; Ratanatharathorn, Voravit; Uberti, Joseph P.; Deol, Abhinav
Abstract: Anti-thymocyte globulin (ATG) targets in-vivo T lymphocytes. Variations in the recipient absolute lymphocyte count (ALC) might result in a variable exposure of ATG. We hypothesized that recipient ALC on the first day of ATG might predict transplant outcomes. We evaluated 217 patients undergoing 8/8 HLA-matched unrelated donor (MUD) peripheral blood stem cell transplant (PBSCT) between January 2005 and December 2017, and receiving rabbit ATG (Thymoglobulin, total dose 4.5 mg/kg) on days −3, −2 and −1. With a median follow up of 3.68 years for survival (OS), one-year OS, relapse rate, non-relapse mortality (NRM), and relapse-free survival (RFS) were 64.7%, 15.9%, 25.8%, and 58.4%, respectively. Multivariable analysis revealed that ALC > 100 k/mm 3 was associated with superior RFS (HR 0.64, p  = .03). Our study indicates that ALC on the first day of thymoglobulin affects relapse-free survival in MUD PBSCT when weight-based thymoglobulin is used.